Impact of equipping with 155 mm self-propelled howitzer systems from the perspective of combat functions - Adrian MIREA (Bulletin of "Carol I" National Defense University)
This article brings into focus a useful way of understanding the impact that 155 mm self-propelled howitzer systems in the prospective equipment of national armed forces could have on the conduct of land force operations. The operational framework described by the warfighting functions is a useful tool to understand how the force commander can capitalize on the available capabilities according to operational needs. In writing this paper, I considered the contribution of 155 mm self-propelled howitzer systems to the fulfilment of each warfighting function from the perspective of friendly forces but, within each function, I have also considered the potential for its disruption, from the enemy’s perspective. In the first part of the article, I briefly presented basic aspects of the warfighting functions and then detailed a perspective on the impact that equipping with 155 mm self-propelled howitzer systems can have on the conduct of land forces operations. Given that these self-propelled howitzer systems employ 155 mm NATO standard ammunition, I have explored in this article the possibility of using the full range of such ammunition without limiting myself to those mentioned in the purchase contract with the Korean manufacturer. Analyzing in this article the impact of equipping with 155 mm self-propelled howitzer systems emphasizes in my view, the usefulness and applicability of the operational framework described by the warfighting functions including in analyzing the potential of any existing or prospective capabilities, whether belonging to friendly forces, to the enemy or belonging to another actor of interest present in the area of operations.